The Relevance of Ecological Values in the Qur'an to the Modern Environmental Crisis - Dewi, Ratna (Fakultas Tarbiyah, IAIN Syaikh Abdurrahman Siddik Bangka Belitung, 2025)
The purpose of this study is to examine verses in the Qur'an that contain ecological values, such as the principles of khalīfah, amanah, mīzān, and the prohibition of fasād (environmental damage). This study is a qualitative study using a library research approach. The results of the study show that the relevance of the Qur'an to the environmental crisis explicitly emphasizes the importance of preserving ecological values in the Qur'an, which include: